PB DIFFUSION IN ZIRCON - Cherniak D.J.; Watson E.B. (My University, 2001)
Diffusion of Pb was characterized in natural and synthetic zircon under a range of conditions. In most experiments, mixtures of Pb sulfate and ground zircon were used as the sources of diffusant, with Pb depth profiles measured with Rutherford Backscattering Spectrometry (RBS). As complement to these “in-diffusion” experiments, “out-diffusion” experiments were run on both synthetic Pb-doped and natural zircon with relatively high Pb concentrations, and analyzed with either electron microprobe or RBS.Over the temperature range 1000–1500°C, the following Arrhenius relation was obtained:Results for diffusion in natural and synthetic zircon were quite similar, as are those for in- and out-diffusion. Pb diffusion does not appear to be strongly influenced by pressure, crystallographic orientation, or the presence of water.The slow diffusion rate for Pb indicates that Pb isotope ratios will not be altered by volume diffusion in crystalline zircon under most geologic conditions, a finding consistent with the frequent observation of inheritance and preservation of multistage histories in zircon. Most Pb loss in zircon, then, is likely a consequence of recrystallization or Pb transport in zircons with severe radiation damage (although the latter can be effective only for vast annealing times at very low temperatures).Mean closure temperatures, calculated from the diffusion parameters, are in excess of 900°C for zircons of typical size, a result in consonance with field-based estimates of closure temperatures.